Air-stable ambipolar organic field-effect transistors based on naphthalenediimide–diketopyrrolopyrrole copolymers1. Issue 25 (21st March 2015) - Wang, Ping; Li, Hui; Gu, Chunling; Dong, Huanli; Xu, Zhenzhen; Fu, Hongbing
<x xml:space="preserve">Abstract</x> A transition from unipolar to ambipolar transport can be achieved by decreasing the thiophene linkers in the backbone of PNDI-mT(DPP)mT.